Chapter 1 From Quantum Physics to Classical Metaphysics - Simpson, William M. R. (Taylor & Francis, 2022)
"In this chapter, I argue that Aristotle's doctrine of hylomorphism, which con- ceived the natural world as consisting of substances which are metaphysically composed of matter and form, is ripe for rehabilitation in the light of quantum physics. I begin by discussing Aristotle's conception of matter and form, as it was understood by Aquinas, and how Aristotle's doctrine of hylomorphism was `physicalised' and eventually abandoned with the rise of microphysicalism. I argue that the phenomenon of quantum entanglement, and the emergence of irreducibly macroscopic phenomena in nite temperature quantum systems, have given us good reasons to doubt the truth of microphysicalism. In support of my argument, I show how to construct a hylomorphic interpretation of the de Broglie-Bohm theory that posits a single Cosmic Substance. I then show how to construct a hylomorphic interpretation of an alternative `contextual' wave function collapse theory (recently proposed by the physicists Barbara Drossel and George Ellis) which posits a plurality of Thermal Substances. Both of these neo-Aristotelian ontologies reject the microphysicalist dogma that nature consists fundamentally of some set of microscopic constituents."